Professionalism of pedagogical persons as one of the conditions of qualitative training of future teachers of technologies - Нevko I. V. (Journal of Education, Health and Sport, 2017)
The article reveals the essence and content of the definitions "professionalism", generalizes the approaches to the definition of professionalism by scientists ofUkraineand other countries, justifies the importance of its achievement by the pedagogical staff, which prepares future teachers of technology. It is proved that the creation of an emotionally-positive mood in the learning environment acts as one of the factors of pedagogical stimulation, in our study, the formation of the professionalism of the future specialist in the technological profile.